1973
DOI: 10.1016/0021-9169(73)90009-3
|View full text |Cite
|
Sign up to set email alerts
|

Counter-electrojet and Esq disappearance

Abstract: The disappearance of Esq type traces from ionograms a t the magnetic equator during magnetically quiet periods is related to inverted latitudinal profiles of the regular daily magnetic 8, variation (in its horizontal and vertical components). Latitude profiles obtained from a meridian chain of nine magnetometers across central Africa me compared with corresponding quarter-hourly ionogram sequences from Fort-Archambault-Sarh (Chad). Between O900 and 1500 LT, the magnetic reversal coincides exactly with the disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…The irregularities' disapearance between 0800 and 0950 UT during the same period of decreasing H and reversed Z (Fig. 1b, d) indicates that a belt of current¯ows in the reverse direction with respect to the normal west-east electrojet ow (Fambitakoye et al, 1973). These E-region irregularities at equatorial latitude giving the appearance of Es-q layer during daytime ionograms have been suggested to be due to cross-®eld instabilities (Rastogi, 1973b).…”
Section: Ionospheric Electrodynamics Datamentioning
confidence: 87%
“…The irregularities' disapearance between 0800 and 0950 UT during the same period of decreasing H and reversed Z (Fig. 1b, d) indicates that a belt of current¯ows in the reverse direction with respect to the normal west-east electrojet ow (Fambitakoye et al, 1973). These E-region irregularities at equatorial latitude giving the appearance of Es-q layer during daytime ionograms have been suggested to be due to cross-®eld instabilities (Rastogi, 1973b).…”
Section: Ionospheric Electrodynamics Datamentioning
confidence: 87%
“…Rastogi et al (1971) showed, for the ®rst time, that the counter electrojet events observed in geomagnetic r ®eld, the absence of i s -q re¯ections in the ionograms and the reversal of the ionospheric drift direction during the daytime hours at an equatorial station were concurrent phenomena. Fambitakoye et al (1973) showed that the reversal of the latitudinal pro®les of Dr and D are the main criterions for the disappearance of i s -q rather than the decrease Dr below its night time level at the equatorial station. Comparing the high resolution modi®ed range time intensity (MRTI) records of VHF backscatter radar echoes at Jicamarca and the magnetograms at Huancayo and Fuquene, Rastogi et al (1977) showed that the E region irregularities disappear precisely (with an accuracy of less than 2 min) when Dr at Huancayo minus Dr at Fuquene decreases below the corresponding night time value.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of the parameter d Sdi defined above we also tried out the simpler parameter 4(HTRI-HALI) considering deviations from pre-dawn level (FAMBITAKOYE et al, 1973). Results were similar to those for d Sdi and hence are not shown here.…”
Section: -2400 Ltmentioning
confidence: 97%